Les Massūfa dans l’Ouest saharien au XIVe siècle, une souveraineté transsaharienne - Hadrien Collet (Afriques)
In the 14th century, West Africa presented a stable political landscape comprised of large sultanates. However, between North Africa and the Sahel, the Sahara is still seen as an area lacking political organizations of any worth, and the nomadic powers are still far from being seen as legitimate authorities over their own territories. Taking the example of the main group in the Saharan West in the fourteenth century, the Massūfa, whose men wore the liṯām, a veil concealing the face, this article proposes a historical and political reading of their trans-Saharan territory. A critical discussion of historiographical prejudices towards Saharan nomads and their space also accompanies the reflection.